Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given that f(x) = x / (x+ (2/x))

The derivative function is given by f'(x) = (Ax^2 + Bx + C) / (x^2+D)^2

where

A=

B=

C=

D=

From rearranging the original equation, I can get D=2 C=0 and A=0, but I cant seem to find B. Maybe someone could help?

EDIT: I found the answer to be 4, but don't see how this makes sense, since I can only clearly see how -2 would work.

share|improve this question
1  
Perhaps start by rewriting the denominator of your given function $f(x)$ as a single fraction. Then rewrite the whole thing as a single fraction. –  Jesse Madnick Jan 31 '11 at 5:49
1  
Your parenthesis in the formula for the derivative are unbalanced, so it is not clear what you have. It is also unclear if $x^2+D$ is to divide just $C$, or the entire $Ax^2+Bx+C$. –  Arturo Magidin Jan 31 '11 at 6:02
    
Thanks I'll fix it –  Finzz Jan 31 '11 at 7:16
    
Why is it you "can't find B"? –  Arturo Magidin Jan 31 '11 at 19:06
    
@ Arturo The system I enter my answers into accepts everything except B = -2 so I figured I was doing something wrong. I guess I will just email my instructor. –  Finzz Jan 31 '11 at 19:53

1 Answer 1

up vote 2 down vote accepted

HINT: Rearrange $f(x) = \frac{x^2}{x^2 + 2} = 1 - \frac{2}{x^2 + 2}$. Use that the derivative of a constant is $0$ and the derivative of $\frac{1}{x^2 + a}$ is $\frac{-2x}{(x^2+a)^2}$.

share|improve this answer
    
Do you mean rearrange the entire equality? Could you prove quick how $f(x) = \frac{x^2}{x^2 + 2} = 1 - \frac{2}{x^2 + 2}$? I know that you rearrange the original f(x) to equal $f(x) = \frac{x^2}{x^2 + 2}$ –  Finzz Jan 31 '11 at 7:22
    
@Sivaram: From there I know that D = 2 and that C is most likely 0 as well as A because we can't use x^2 and don't need a constant of C, so that means B has to be -2? –  Finzz Jan 31 '11 at 7:29
    
@Finzz: to get the equality of $f(x)$, just add a "clever $0$" to the numerator and break up the sum: $$\frac{x^2}{x^2+2} = \frac{x^2+(2-2)}{x^2+2} = \frac{(x^2+2)-2}{x^2+2} = \frac{x^2+2}{x^2+2} - \frac{2}{x^2+2} = 1 - \frac{2}{x^2+2}.$$And, yes, for $\frac{Ax^2+Bx+C}{(x^2+D)^2}$ to be equal to $$\frac{-2x}{(x^2+2)^2}=\frac{0x^2 -2x +0}{(x^2+2)^2},$$you need the numerator and denominators to be identical. –  Arturo Magidin Jan 31 '11 at 16:55
    
@Arturo: Right, thanks. that's exactly how I did it, but the system I enter my answers into accepts everything except B = -2 so I will email my instructor. –  Finzz Jan 31 '11 at 19:31
    
He said I went wrong with my quotient rule. :S –  Finzz Jan 31 '11 at 21:38

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.